PENGARUH PERUBAHAN DIVIDEND PAYOUT RATIO DAN DIVIDEND YIELD TERHADAP RETURN SAHAM (STUDI PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA) - Linda Purnamasari (STIE Perbanas Surabaya, 2013)
This research aims to determine the effect of dividend payout ratio and dividend yield on stock price. Population taken consists of all manufacturing companies listed in the Indonesia Stock Exchange (IDX). From this, the sample was taken comprising 23 companies. This took a period from 2007 to 2011, using purposive sampling method with simple regression analysis test tools. It was found the dividend payout ratio both increased and decreased but did not have a significant effect on stock prices in which the dividend yield decreased. However, in testing the hypothesis dividend yield increase, it was also found that there was a significant effect on stock prices. Such finding was due to absence of force of dividend signaling theory in Indonesia; the prevailing theory is theory of rent extraction hypothesis.